Water mass denitrification during the latest Permian extinction in the Sverdrup Basin, Arctic Canada - Knies, Jochen; Grasby, Stephen E.; Beauchamp, Benoit; Schubert, Carsten J. (Geology, 2013)
ISSN:0091-7613 ISSN:1943-2682